Feeding the fire: Annual grass invasion facilitates modeled fire spread across Inland Northwest forest‐mosaic landscapes. Issue 2 (8th February 2023) - Tortorelli, Claire M.; Kim, John B.; Vaillant, Nicole M.; Riley, Karin; Dye, Alex; Nietupski, Ty C.; Vogler, Kevin C.; Lemons, Rebecca; Day, Michelle; Krawchuk, Meg A.; Kerns, Becky K.
Abstract: Invasive annual grasses are a growing global concern because they facilitate larger and more frequent fires in historically fuel‐limited ecosystems. Forests of the western United States have remained relatively resistant to invasion by annual grasses and their subsequent impacts. However, where forests are adjacent to invaded areas, increased fire spread across ecotones could alter fire behavior and ecosystem resilience. In the Inland Northwest, USA, recent invasion by the annual grass ventenata ( Ventenata dubia ) has increased fine fuel loads and continuity in nonforest patches embedded within the forested landscape. Despite ventenata's rapid spread across the American West and growing management concern, little is known regarding how invasion influences fire within invaded vegetation types or its potential to alter landscape‐scale fire and management practices. Here, we examine how the ventenata invasion alters simulated fire across forest‐mosaic landscapes of the 7 million ha Blue Mountains Ecoregion using the large fire simulator (FSim) with custom fuel landscapes: present‐day invaded versus historic uninvaded. Invasion increased simulated mean fire size, burn probability, and flame lengths throughout the ecoregion, and the strength of these impacts varied by location and scale. Changes at the ecoregion scale were relatively modest given that fine fuels increased in only 2.8% of the ecoregion where ventenata invaded historically fuel‐limited vegetation types. However, strong localized changes were simulated within invaded patches (primarily dwarf‐shrublands) and where invasion facilitated fire spread into nearby forests. Within invaded patches, burn probabilities increased by 45%, and higher flame lengths required fire management strategies to shift from direct to indirect attack, requiring large machinery. Forests with 25% of their neighborhood invaded experienced a 28% increase in burn probability and 16% increase in the probability of experiencing flame lengths likely to produce crown fire (flame lengths >2.4 m). Increased canopy loss could have severe implications for forest resilience given that invasive grasses can heavily invade early seral dry conifer forests and limit postfire forest recovery. Our study demonstrates how annual grass invasion can influence fire behavior and resilience across forest landscapes despite primarily invading nonforested areas, and highlights invasion as an important management issue in an expansive forest‐mosaic ecosystem.